Effects of different rest intervals between sets on muscle performance in the leg press exercise in untrained elderly women - Jambassi Filho, José Claudio [UNESP]; Gurjão, André Luiz Demantova [UNESP]; Ceccato, Marília [UNESP]; Gonçalves, Raquel [UNESP]; Gallo, Luiza Hermínia [UNESP]; Gobbi, Sebastião [UNESP] (FapUNIFESP (SciELO), 2012)
Objective: to assess the influence of two different rest intervals (RI) between sets in the leg-press exercise on the number and sustainability of repetitions and total volume in untrained elderly women. Methods: eleven untrained elderly women (66.5 ± 5.0 years; 59.2 ± 9.1 kg; 146.4 ± 34.9 cm) were submitted to two experimental sessions of resistance exercise with intensity of 15 maximum repetitions. Each experimental session consisted of three sets performed until muscle fatigue with an RI of one (RI-1) or 3 minutes (RI-3). The experimental sessions were separated by at least 48 hours. All participants performed both protocols and a balanced cross-over outlining was used to determine the experimental sessions order. Results: for both RI between sets, significant reduction (P < 0.05) in the number and sustainability of repetitions was observed from the first to the second and third sets, and the second to the third sets. Significant differences (P < 0.05) between the RI were observed in the two final sets. The total volume of the session with RI-3 was statistically higher (20.4%, P < 0.05) when compared with RI-1 session. Conclusion: the number and sustainability of repetitions and the total volume of training in untrained elderly women are influenced by the RI employed between sets. Longer RI should be used when the training goal is to increase training volume through the sustainability of repetitions. Conversely, a shorter RI should be used when the goal is to obtain higher levels of muscle fatigue.
Keywords: Aging; Muscle endurance; Muscle fatigue; Resistance exercise